2021
DOI: 10.1002/dev.22157
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an automated gaze‐controlled paradigm for capturing neural responses during visual and face processing in toddlerhood

Abstract: Electroencephalography (EEG) has substantial potential value for examining individual differences during early development. Current challenges in developmental EEG research include high dropout rates and low trial numbers, which may in part be due to passive stimulus presentation. Comparability is challenged by idiosyncratic processing pipelines. We present a novel toolbox ("Braintools") that uses gaze-contingent stimulus presentation and an automated processing pipeline suitable for measuring visual processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Both Morales et al. (2022) and Haartsen and colleagues (2021) describe standardized pipelines for processing and quantification of response‐locked brain activity, each making efforts to streamline data processing procedures in ways that minimize lab‐to‐lab variability and allow for more direct comparisons across studies.…”
Section: New Approaches To Data Processing and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Morales et al. (2022) and Haartsen and colleagues (2021) describe standardized pipelines for processing and quantification of response‐locked brain activity, each making efforts to streamline data processing procedures in ways that minimize lab‐to‐lab variability and allow for more direct comparisons across studies.…”
Section: New Approaches To Data Processing and Quantificationmentioning
confidence: 99%
“…Haartsen et al. (2021) offer an innovative approach using gaze‐contingent stimulus presentation to ensure that young children are attending to stimuli as EEG/ERP data are recorded.…”
Section: Novel Eeg/erp Paradigms and Engagement Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The battery will begin with a quasi‐resting‐state task in which the children will view a video of abstract shapes while their EEG activity is recorded; this video 33 was developed specifically for collecting resting‐state neuroimaging data from young children and is used in our other studies of early child development. The second task involves passive viewing of photographic images of female faces showing neutral facial expressions (four different females will be used, each of a different racial or ethnic background, taken from the RADIATE face stimulus set 34 ) and black and white checkerboard patterns; this task reliably elicits neural indices of face processing versus more general visual processing and is commonly used in studies examining the development of social communication abilities 35 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, having eye-tracking removes the need for collecting videos of the child for later manual gaze coding; this improves the potential for scalability and reduces the privacy concerns raised by capturing images of the child in their home setting. A recent study in a HIC and laboratory-based setting demonstrated this gaze-contingent stimulus presentation results in low drop-out rates and results in moderate test-retest reliability of neural responses in young toddlers 23 .…”
Section: Introductionmentioning
confidence: 98%